The Pseudomonas syringae HopPtoV Protein Is Secreted in Culture and Translocated into Plant Cells via the Type III Protein Secretion System in a Manner Dependent on the ShcV Type III Chaperone - Wehling, Misty D. (American Society for Microbiology, 2004)
The bacterial plant pathogen Pseudomonas syringae depends on a type III protein secretion system and the effector proteins that it translocates into plant cells to cause disease and to elicit the defense-associated hypersensitive response on resistant plants. The availability of the P. syringae pv. tomato DC3000 genome sequence has resulted in the identification of many novel effectors. We identified the hopPtoV effector gene on the basis of its location next to a candidate type III chaperone (TTC) gene, shcV, and within a pathogenicity island in the DC3000 chromosome. A DC3000 mutant lacking ShcV was unable to secrete detectable amounts of HopPtoV into culture supernatants or translocate HopPtoV into plant cells, based on an assay that tested whether HopPtoV-AvrRpt2 fusions were delivered into plant cells. Coimmunoprecipitation and Saccharomyces cerevisiae two-hybrid experiments showed that ShcV and HopPtoV interact directly with each other. The ShcV binding site was delimited to an N-terminal region of HopPtoV between amino acids 76 and 125 of the 391-residue full-length protein. Our results demonstrate that ShcV is a TTC for the HopPtoV effector. DC3000 overexpressing ShcV and HopPtoV and DC3000 mutants lacking either HopPtoV or both ShcV and HopPtoV were not significantly impaired in disease symptoms or bacterial multiplication in planta, suggesting that HopPtoV plays a subtle role in pathogenesis or that other effectors effectively mask the contribution of HopPtoV in plant pathogenesis.